2011
DOI: 10.3109/08958378.2010.543188
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of the toxicology of cigarette ingredients: essential oils and resins

Abstract: The essential oils and resins tested here as ingredients in experimental cigarettes show minimal toxicological sequelae, even at high inclusion levels. The highest inclusion level for SO showed some equivocal responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Many of the 'smoke-related' observations made from assaying both the kretek cigarettes and the Americanblended reference cigarette 2R4F in the present study were similar to those reported from several MS inhalation studies in rats (Baker et al, 2004;Coggins et al, 2011;Roemer et al, 2012;Terpstra et al, 2003;Vanscheeuwijck et al, 2002). However, there are notable differences between kretek cigarette smoke-exposed groups and the groups exposed to smoke from the reference cigarette 2R4F.…”
Section: Discussionsupporting
confidence: 89%
“…Many of the 'smoke-related' observations made from assaying both the kretek cigarettes and the Americanblended reference cigarette 2R4F in the present study were similar to those reported from several MS inhalation studies in rats (Baker et al, 2004;Coggins et al, 2011;Roemer et al, 2012;Terpstra et al, 2003;Vanscheeuwijck et al, 2002). However, there are notable differences between kretek cigarette smoke-exposed groups and the groups exposed to smoke from the reference cigarette 2R4F.…”
Section: Discussionsupporting
confidence: 89%
“…This also is consistent with single cigarette-ingredient studies involving guar (Coggins et al, 2011) and propylene glycol (Gaworski et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…For these studies, two lots of starting material and different amounts of guar (Coggins et al, 2011) and propylene glycol (Gaworski et al, 2010) were used to make the Deli cast sheet that was incorporated into experimental cigarettes. As two lots of starting material were used, a comparison of these lots was also performed using two additional experimental cigarettes (Table 1).…”
Section: Cigarette Construction and Smokingmentioning
confidence: 99%
“…The NTP attributed its finding to reflux of the gavage material. Third, deep lung effects are measurable in animals exposed to cigarette smoke as indicated by the glycerol triacetate study (Coggins et al, 2011c). Pigmented macrophages are common findings at the end of the 90-day exposure period, and at the end of the non-exposure recovery period.…”
Section: Inhalationmentioning
confidence: 98%